2019
DOI: 10.1155/2019/7919836
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pretreatment Serum Uric Acid Levels and Progression of Newly Diagnosed Primary Angle-Closure Glaucoma: A Prospective Cohort Study

Abstract: Purpose. Increased evidence reveals that uric acid (UA) may have an important neuroprotective effect through its antioxidant properties. The aim of the present study was to investigate the relationship between pretreatment serum UA levels and the progression of newly diagnosed primary angle-closure glaucoma (PACG). Methods. This prospective observational cohort study included 64 patients with newly diagnosed PACG who were followed up for a mean period of 12.77 months (range: 3–28 months). All subjects underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
1
16
0
1
Order By: Relevance
“…The previously described methods were used for the VF analysis as follows [ 13 ]. The Glaucoma Department of the Eye and ENT Hospital of Fudan University performed perimetry on the glaucoma subjects unless they were unable to see any light with both eyes open or suffered from an eye infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously described methods were used for the VF analysis as follows [ 13 ]. The Glaucoma Department of the Eye and ENT Hospital of Fudan University performed perimetry on the glaucoma subjects unless they were unable to see any light with both eyes open or suffered from an eye infection.…”
Section: Methodsmentioning
confidence: 99%
“…PACG was diagnosed by a glaucoma specialist. Previously described diagnostic criteria were used to diagnose PACG [13][14][15][16][17]. PACG was diagnosed based on narrow anterior chamber angles with glaucomatous optic neuropathy and corresponding VF loss.…”
Section: Diagnostic and Inclusionmentioning
confidence: 99%
“…PACG was diagnosed by a glaucoma specialist. Previously described diagnostic criteria were used to diagnose PACG and previously described inclusion criteria were used to select patients ( 11 13 ). PACG was diagnosed based on narrow anterior chamber angles with glaucomatous optic neuropathy and corresponding VF loss.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that high serum uric acid levels within the normal range may have a protective role against the primary angle-closure glaucoma (PACG). [24][25][26] In their cross-sectional and case-control studies, the uric acid levels are within normal range, and the PACG patient has lower uric acid levels whereas the non-PACG patient has high baseline serum uric acid levels. These studies propose that uric acid may have an important neuroprotective effect through its antioxidant properties.…”
Section: No Of Glaucomamentioning
confidence: 99%